Sympathetic Effect of Auricular Transcutaneous Vagus Nerve Stimulation on Healthy Subjects: A Crossover Controlled Clinical Trial Comparing Vagally Mediated and Active Control Stimulation Using Microneurography - Gauthey, Anaïs; Morra, Sofia; van de Borne, Philippe; Deriaz, Denis; Maes, Nathalie; le Polain de Waroux, Jean-Benoît (Frontiers in Physiology, 2020)
Introduction: Auricular low-level transcutaneous vagus nerve stimulation (aLL-tVNS) has emerged as a promising technology for cardiac arrhythmia management but is still experimental. In this physiological study, we hypothesized that aLL-tVNS modulated the autonomic nervous balance through a reduction of sympathetic tone and an increase in heart rate variability (HRV). We investigated the muscle sympathetic nerve activity (MSNA) recorded by microneurography during vagally-mediated aLL-tVNS and active control on healthy volunteers. Methods: In this crossover, double-blind controlled study, healthy men (N=28; 27 ± 4 years old) were assigned to aLL-tVNS applied to cymba and lobe (active control) of the right ear. Each participant was randomly allocated to the three sequences (5Hz, 20Hz and active control-5Hz) during one session. MSNA signal was recorded at rest, during voluntarily apnea and aLL-tVNS. Sympathetic activity was expressed as: 1) number of bursts per minute (burst frequency: BF) and 2) MSNA activity calculated as BF x mean burst amplitude and expressed as changes from baseline (%). RR intervals, HRV parameters and sympathetic activity were analyzed during 5min-baseline, 10min-stimulation and 10min-recovery periods. Mixed regression models were performed to evaluate cymba-(5Hz-20Hz) effects on the parameters with stimulation. Results: During apnea and compared to baseline, BF and MSNA activity increased (p =0.002, p =0.001, respectively). No stimulation effect on RR intervals and HRV parameters were showed excepted a slightly increase of the LF/HF ratio with stimulation in the cymba-5Hz sequence (coef. ± SE: 0.76 ± 0.32%; p=0.02). During stimulation, reductions from baseline in BF (Coef. ± SE: -4.8 ± 1.1, p<0.001) was observed but was not statistically different from that one in the active control. Reduction of MSNA activity was not significantly different between sequences. Conclusion: Acute right cymba aLL-tVNS did not induce any overall effects neither on heart rate, HRV nor MSNA variables on healthy subjects when compared to active control. Interestingly, these findings questioned the role of active controls in medical device clinical trials that implied subjective endpoints.